Analyzing the Role of Agricultural Extension Agents in Transfer of Improved Technologies Regarding Citrus Production (Sweet Orange) In District Malakand: https://doi.org/10.55966/assaj.2025.4.1.0113 - Furqan Shafiq; Shah Hassan (`, 2025)
This study examines the role of agricultural extension agents in facilitating the transfer of improved technologies for citrus (sweet orange) production in District Malakand, Khyber Pakhtunkhwa, Pakistan. Citrus farming is a vital economic activity in the region, yet productivity remains below potential due to inadequate dissemination of modern agricultural practices. The research aims to evaluate the linkage between citrus growers and the agricultural extension department, assess the effectiveness of extension services, identify key constraints in technology adoption, and propose recommendations for enhancing service delivery. A structured survey was conducted among 90 citrus growers from two major citrus-producing union councils, Palai and Wartair, using proportionate sampling. Data were analyzed through SPSS, employing frequency distributions and chi-square tests. The findings reveal that while most farmers were engaged in citrus cultivation, their access to and application of improved technologies are limited. Key issues include low literacy rates, insufficient extension agent visits, poor marketing knowledge, and financial constraints. The role of extension agents was found to be suboptimal, both in moral and mandatory dimensions. Farmers highlighted the need for frequent extension visits, training programs, and improved input availability. The study concludes with policy recommendations including enhanced training for extension agents, improved infrastructure support, the use of demonstration plots, and stronger institutional linkages to boost citrus productivity and farmer livelihoods. Keywords: Agricultural Extension, Technology Transfer, Citrus Production, Sweet Orange, district Malakand